Using factor models to construct composite indicators from BCS Data : a comparison with European Commission Confidence Indicators - Gayer, Christian; Genet, Julien; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
This paper compares different approaches to constructing composite business cycle indicators based on series from the Joint Harmonised EU Programme of Business and Consumer Surveys (BCS). The currently computed Confidence Indicators are used as benchmarks in gauging four different factor-analytic methods to extract sectoral business cycle indicators. Improvements in tracking performance are mainly found on individual country level.
Economic Papers